Investigating the essential oil composition of Ducrosia anethifolia (DC.) Boiss. in differnet altitudes of Sistan and Baluchestan province, Iran - Mina Arbabi; Hassanali Naghdi Badi; Mohammadreza Labbafi; Ali Mehrafarin; Ebrahim Saboki (Institue of Medicinal Plants, ACECR, 2020)
Background: The content and composition of effective components of medicinal plants in different natural habitats are affected by various factors such as elevation of sea level. Objective: The aim of this study was to investigate the effects of altitude of sea level on the essential oil composition of Ducrosia anethifolia Boiss in its natural habitats in Sistan and Baluchestan province, Iran. Methods: The plant aerial parts were gathered at full flowering stage from four different altitudes including altitudes of 0-400, 800-400, 800-800 and 1600-1200 meters above sea level and dried in shade. The essential oil was extracted by the hydro-distillation method by Clevenger-type apparatus. The composition of the essential oil was determined by combined GC/MS and GC. Results: Results showed that habitat height had a significant effect on the essential oils composition and cis-Chrysanthenyl acetate with an average of 44.77% was the main component, which was observed at 0-400 and 400- 800 m above sea level. Also, n-Decanal, α-Pinene, Citronellal, and p-Cymene were 7.59%, 3.37%, 2.70% and 1.91% of the other main components, respectively. The amounts of these compounds at various altitudes were significantly different. Conclusion: A significant relationship between the altitude of sea level and essential oil components of Ducrosia anethifolia were observed. Also, sea level elevation was an important factor in changes of essential oil composition of this plant.